1967
DOI: 10.1111/j.2042-7158.1967.tb08028.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of cardio-active substances by plant tissue cultures and their screening for cardiovascular activity

Abstract: Semi‐purified extracts of six plant tissue cultures were examined for their effects on respiration, heart rate, and blood pressure in anaesthetized rabbits. Ammi visnaga, Cheiranthus cheiri, Digitalis lanata, and Urginea maritima evoked pronounced vasodilatation and bradycardia which ultimately resulted in the death of the animal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Later chromatograms were exposed to I 2 vapours, marked, evaporated and these spots were scraped and the compounds eluted with chloroform and concentrated. Each of the compounds were crystallized with methanol and acetone (1:2; Kaul et al , 1967). The crystals were dried in vacuo and subjected to melting point and various physical and spectral studies for characterization (Heilbron and Bunbury, 1953;Yamaguchi, 1970).…”
Section: Methodsmentioning
confidence: 99%
“…Later chromatograms were exposed to I 2 vapours, marked, evaporated and these spots were scraped and the compounds eluted with chloroform and concentrated. Each of the compounds were crystallized with methanol and acetone (1:2; Kaul et al , 1967). The crystals were dried in vacuo and subjected to melting point and various physical and spectral studies for characterization (Heilbron and Bunbury, 1953;Yamaguchi, 1970).…”
Section: Methodsmentioning
confidence: 99%
“…This preparative TLC was repeated until sufficient crystallizable quantities could be obtained of each of the substance (Fried and Sherma, 1986). Each of the isolated compounds was crystallized with methanol: acetone (1:2; Kaul et al, 1967). The standards were obtained from the Natural Products Laboratory, Department of Chemistry, University of Rajasthan, Jaipur.…”
Section: Quantification Of Triterpenoidsmentioning
confidence: 99%
“…The spots separated by TLC were scraped from the plate with sorbent and the compound was eluted with chloroform and concentrated (Coscia, 1984). Each of the compounds was crystallized with methanol : acetone (1:2; Kaul et al, 1967). These crystals were dried in vacuo and subjected to various physical and spectral studies for characterization (Heilbron and Bunbury, 1953;Yamaguchi, 1970).…”
Section: Quantification Of Triterpenoidsmentioning
confidence: 99%
“…Cardioactive glycosides have been isolated from the bulb of white squill plant, Urginea maritima (LINNB) BAKER [I], and they have been structurally elucidated [I-31 and pharmacologically examined [4-71. KAUL et al reported that semipurified extracts of a squill tissue culture established from withe squill bulbs produced a pronounced vasodilatation and bradycardia in anaesthetized rabbits [8]. T h e objective of this study was to examine similar cemi-purified extracts for the presence of bufadienolides, anthocyanins and other compounds.…”
Section: Introductionmentioning
confidence: 95%